Peran SDM dalam Pengelolaan Sektor Perikanan Terhadap Pendapatan Masyarakat di Kota Pasuruan - Dwi Nur Aini; Mailani Amriatul Aulia; Nurus Sobakh (Indo Publishing, 2026)
The fisheries sector in Pasuruan City has significant potential to support the coastal economy, supported by its strategic geographic location and abundant marine resources. However, this potential has not been optimally utilized due to a gap between the availability of natural resources and the quality of the human resources (HR) managing them. These challenges include low human resource quality, the use of traditional production methods, limited innovation in fisheries processing, and a marketing system that relies heavily on middlemen. This study aims to analyze the role of human resource quality in improving productivity and community welfare in the fisheries sector in Pasuruan City. The method used is a literature review, reviewing various relevant previous studies. The results indicate that human resource quality is a key factor in increasing productivity, business efficiency, and the added value of fishery products. Furthermore, the use of technology and strengthening business institutions play a crucial role in expanding market access and increasing the competitiveness of business actors. Therefore, improving human resource quality through training, mentoring, and technology utilization is a key strategy in optimizing the potential of the fisheries sector. These efforts are expected to increase productivity, strengthen competitiveness, and encourage sustainable improvements in the welfare of coastal communities.